Cubic to pseudo-cubic tetragonal phase transformation with Mg, Ca, and Be doping and its impact on optoelectronic, elastic and mechanical properties of SrHfO3. (June 2023) - Abbas, Nooria; Zeba, I.; Shakil, M.; Gulzar, Fakiha; Ahmad, Riaz; Gillani, S.S.A.
Abstract: The structural, optoelectronic, elastic and mechanical properties of pure, Ca-, Mg-, and Be-doped SrHfO3 have been computed with CASTEP code based on density functional theory. The structure of SrHfO3 remains cubic with 1.40% doping concentration of Ca, Mg and Be whereas it is altered in pseudo-cubic tetragonal at the doping concentration of 4.22% and 7.04%. Reduction in the electronic band gap is observed in all the doping concentrations. For detailed explanation of electronic band gap reduction density of states (DOS), partial DOS and elemental partial DOS have also been computed. DOS plays a very meaningful role in understanding the behavior of band gap at different doping. The impact of dopants on the optical properties of pure SrHfO3 indicates the increment in refractive index ( n ), absorption ( I ), Loss function (L) and extinction coefficient ( k ) as well. For both cubic and tetragonal structures our compound shows mechanical stability in all doping percentages of Ca, Mg and Be other than the 1.40% of Mg and Be for cubic geometry. Over and above that to examine the mechanical properties of material like ductility and brittleness we have also computed the different characteristics such as Bulk modulus ( B ), Shear modulus ( G ), G / B ratio, Cauchy Pressure ( CP ) and Anisotropic factor ( A ). Interestingly, the material is purely ductile on all concentrations of Ca, Mg, and Be and shows brittleness only at the doping concentration of 1.40% of Ca. Graphical abstract: Image 1 Highlights: The GGA-PBE correlation functional is used to estimate the structural, electronic, optical, elastic and mechanical characteristics of SrHfO3 . Cubic to pseudo-cubic phase transition is observed. Band gap is direct in its nature except at 4.22% doping concentration. Due to approaching trend of compound from semiconductor to conductor, makes it an excellent choice for various photovoltaic applications. Mechanically SrHfO3 has stable form, less compressible, ductile in nature and has anisotropic character.